Shot peening increases resistance to cyclic fatigue fracture of endodontic files - Javier Nino-Barrera (Nature Portfolio, 2021)
Abstract The objective of this study was to assess the resistance to fatigue fracture of conventional nickel–titanium files after undergoing shot peening. Forty NITIFLEX endodontic files, number 30, were divided into two groups; one was submitted to shot peening treatment and the other was not. All instruments were tested for fatigue fracture in simulated canals with a TRI-AUTO ZX endodontic motor. One file of each group was subjected to a residual stress analysis by XRD. Finally, the fractured surface was observed and elemental analysis performed by means of SEM and EDX. Roughness analysis was made by focal variation microscope. The shot peening group showed greater resistance to fatigue fracture; there was no difference in the length of the fractured fragments. XRD results showed the presence of residual compression stresses in the file submitted to shot peening, a decrease in the interplanar spacing, and an increase in the full-width-at-half-maximum and the microstrains. SEM and EDX showed a ductile fracture with zones of fatigue and an equiatomic ratio between the nickel and titanium. Surface roughness increased after the file was subjected to the shot peening procedure. In conclusion, shot peening increases the resistance to fatigue fracture due to the presence of residual compression stresses in files manufactured from a conventional nickel–titanium alloy.